Cost of co-infection controlled by infectious dose combinations and food availability - Fellous, Simon; Koella, Jacob C (My University, 2010)
To what extent the combined effect of several parasite species co-infecting the same host (i.e. polyparasitism) affects the host’s fitness is a crucial question of ecological parasitology. We investigated whether the ecological setting can influence the co- infection’s outcome with the mosquito Aedes aegypti and two parasites: the microsporidium Vavraia culicis and the gregarine Ascogregarina culicis. The cost of being infected by the two parasites depended on the interaction between the two infectious doses and host food availability. The age at pupation of the mosquito was delayed most when the doses of the two parasites were highest and little food was available. As infectious dose increases with the parasites’ prevalence and intensity of transmission, the cost of being co-infected depends on the epidemiological status of the two parasite species.
Keywords: Co-infection; Infectious dose; Virulence; Ecology; Epidemiology